2015
DOI: 10.1126/scitranslmed.aac4877
|View full text |Cite
|
Sign up to set email alerts
|

Improving the spatial resolution of epiretinal implants by increasing stimulus pulse duration

Abstract: Retinal prosthetic implants are the only approved treatment for retinitis pigmentosa, a disease of the eye that causes blindness through gradual degeneration of photoreceptors. An array of microelectrodes triggered by input from a camera stimulates surviving retinal neurons, each electrode acting as a pixel. Unintended stimulation of retinal ganglion cell axons causes patients to see large, oblong shapes of light, rather than focal spots, making it difficult for them to perceive forms. To address this problem,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
215
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(238 citation statements)
references
References 50 publications
(131 reference statements)
15
215
1
2
Order By: Relevance
“…In a study of rat retina in vitro, Weitz et al reported that a sinusoidal pulse has a lower threshold charge than does a rectangular one. (13) However, this result was obtained using epiretinal stimulation; therefore, the effect of a sinusoidal pulse in STS has not been established. In addition, these in vitro results may not hold true in vivo.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…In a study of rat retina in vitro, Weitz et al reported that a sinusoidal pulse has a lower threshold charge than does a rectangular one. (13) However, this result was obtained using epiretinal stimulation; therefore, the effect of a sinusoidal pulse in STS has not been established. In addition, these in vitro results may not hold true in vivo.…”
Section: Introductionmentioning
confidence: 81%
“…Weitz et al reported that the threshold charge at which retinal ganglion cells fired was 22.8 ± 35.5% greater for a rectangular pulse than for a sinusoidal pulse. (13) In their in vitro study, they applied direct stimulation to the ganglion cell side of the retina. Although this methodology differed from ours, the results are similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These specific-shaped phosphenes can also be generated by the activation of ganglion cell axons [30]. Retinal ganglion cell axons pass within short distances from each other along their path to the brain.…”
Section: Discussionmentioning
confidence: 99%
“…To evoke a narrow spot of light that resembles a natural signal to the brain and can serve as a building block for the pattern of phosphenes, each electrode should activate a nearby cell [30].…”
Section: Introductionmentioning
confidence: 99%